2013
DOI: 10.1111/jan.12107
|View full text |Cite
|
Sign up to set email alerts
|

A concept analysis of oral hygiene care in dependent older adults

Abstract: Clarity around the concept of oral hygiene care as a nursing intervention could enable nurses to impact oral health outcomes and possibly prevent systemic diseases in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Oral care encloses screening and identification of oral health problems, dental treatment and daily oral hygiene (MacEntee, Thorne, & Kazanjian, ). Oral hygiene involves inspection of the mouth, removing plaque and biofilm from gums and tissues in the oral cavity and cleaning the oral gums and tissues and cavity (Coker, Ploeg, Kaasalainen, & Fisher, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral care encloses screening and identification of oral health problems, dental treatment and daily oral hygiene (MacEntee, Thorne, & Kazanjian, ). Oral hygiene involves inspection of the mouth, removing plaque and biofilm from gums and tissues in the oral cavity and cleaning the oral gums and tissues and cavity (Coker, Ploeg, Kaasalainen, & Fisher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides these direct effects in the oral cavity, impaired oral health can lead to further deterioration of patient's health status. Associations are found with diabetes (Azarpazhooh & Tenenbaum, ), cardiovascular diseases (Azarpazhooh & Tenenbaum, ; Beck, Garcia, Heiss, Vokonas, & Offenbacher, ; Senpuku et al, ; Virtanen et al, ; Ylostalo, Jarvelin, Laitinen, & Knuuttila, ), stroke (Wu et al, ), pneumonia (Azarpazhooh & Tenenbaum, ; Pace & McCullough, ; Quinn et al, ; Senpuku et al, ; Sjogren et al, ) and postoperative infections (Bartzokas et al, ; Sato et al, ), especially in older patients (Coker et al, ; Senpuku et al, ; Sjogren et al, ). Impaired oral health limits people's ability to eat, smile and speak, psychosocial well‐being and quality of life (Coleman, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More residents of care facilities are at least partially dentate and the teeth they have present with more complex tooth‐ and implant‐supported restorations and dentures . The residents are often medically and cognitively compromised and poly medicated placing them at higher risk for oral conditions such as dental caries, gingival diseases and denture‐related fungal infections. In addition, oral health and general health links have been reported: with compromised oral health associated with respiratory diseases, cardiovascular diseases, diabetes and possibly stroke .…”
Section: Introductionmentioning
confidence: 99%
“…In residential care facilities in Australia, PCAs provide the majority of personal hygiene care for residents including oral hygiene practices . Research has shown that oral hygiene care status in residents with dementia was poor despite established guidelines for oral care and the fact that oral care assistance was being provided . A number of studies suggest that the personal attitudes and values of PCAs related to oral hygiene remain one of the most significant barriers to residents receiving adequate oral health assistance .…”
Section: Introductionmentioning
confidence: 99%